490. Comparison of Clostridium difficile Infection Outcomes by Diagnostic Testing Method. (26th November 2018) - Guh, Alice; Hatfield, Kelly; Winston, Lisa G; Martin, Brittany; Johnston, Helen; Brousseau, Geoff; Farley, Monica M; Wilson, Lucy E; Perlmutter, Rebecca; Phipps, Erin C; Dumyati, Ghinwa; Nelson, Deborah; et al.
Abstract: Background: US laboratories are increasingly using nucleic acid amplification tests (NAAT) to diagnose Clostridium difficile infection (CDI) due to their increased sensitivity over toxin enzyme immunoassays (EIA), but NAATs may be more likely than toxin EIAs to detect colonization rather than true disease. Limited data indicate patients positive by toxin EIA (toxin+) have worse outcomes than those positive by NAAT (NAAT+) only, suggesting toxin EIA detects true infection more often than NAAT. We used multisite CDI surveillance data from the Centers for Disease Control and Prevention's Emerging Infections Program to compare clinical course and outcomes between toxin+ and NAAT+ only patients. Methods: A case was defined as a positive C. difficile test in a person ≥1 year old with no positive tests in the prior 8 weeks. Cases detected during 2014–2015 by a testing algorithm using toxin EIA and NAAT were classified as toxin+ or NAAT+ only. Medical charts were reviewed. Death data were obtained from state death registries. Multivariable logistic regression models were used to compare CDI recurrence and 90-day mortality between the two groups, adjusting for age, sex, race, Charlson comorbidity index, and receipt of oral vancomycin. For the outcome of recurrence, we also adjusted for history of CDI in the prior 6 months. Results: Of 4, 878 cases, 2160 (44%) were toxin+ and 2, 718 (56%) were NAAT+ only. Toxin+ cases were more likely than NAAT+ only cases to be ≥65 years old (48% vs. 38%; P < 0.0001), have white blood cells ≥15, 000/µL (483/1, 539 [31%] vs. 423/1, 978 [21%]; P < 0.0001), and have received oral vancomycin ≤3 days of diagnosis (32% vs. 29%; P = 0.03). Comparing toxin+ to NAAT+ only cases, 21% vs. 11% had a recurrence ( P < 0.0001), of which 71% vs. 33% had a toxin+ recurrence ( P < 0.0001), and 10% vs. 9% died ≤90 days of diagnosis ( P = 0.12). In multivariable analysis, a toxin+ result was associated with recurrence (adjusted odds ratio [aOR]: 1.89, 95% CI: 1.61–2.22) but not with 90-day mortality (aOR: 0.99; 95% CI: 0.81–1.22). Conclusion: Toxin+ CDI is more severe by some markers and more likely to recur as toxin+. However, there was no difference in adjusted mortality, which may reflect an effect on mortality in NAAT+ only cases from mild CDI, receipt of unnecessary CDI treatment, or other factors. Disclosures: G. Dumyati, Seres: Scientific Advisor, Consulting fee.